2016
DOI: 10.4236/sn.2016.51003
|View full text |Cite
|
Sign up to set email alerts
|

Using IQA to Extract Mental Models Concerning Quality Evaluation Factors for Social Networking Services on Smartphones

Abstract: Although today's users of mobile phones are afforded increasing control as the popularity and richness of information provided by smartphones increases, how these users make choices and evaluations cannot be explicitly expressed. This study uses an acute observation of designers of technology and aesthetics to conduct a mental-model analysis of smartphones with the purpose of explicitly identifying the differences in the schemas of users. This study also modifies the mental model to evaluate the practicability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Good examples of IQA research reports can be found in Harrel (2004), Robertson (2015), and Davis (2019). The works of Bargate (2014) and Lee and Chen (2016) are more focused on the presentation of the resulting mind maps and not so much on descriptions of affinities and relationships. Figure 10 shows the flow of a survey conducted from the interactive qualitative analysis.…”
Section: Individual Interviews: Understanding the Concepts And Relati...mentioning
confidence: 99%
“…Good examples of IQA research reports can be found in Harrel (2004), Robertson (2015), and Davis (2019). The works of Bargate (2014) and Lee and Chen (2016) are more focused on the presentation of the resulting mind maps and not so much on descriptions of affinities and relationships. Figure 10 shows the flow of a survey conducted from the interactive qualitative analysis.…”
Section: Individual Interviews: Understanding the Concepts And Relati...mentioning
confidence: 99%